Carbon nitride from urea: mechanistic study on photocatalytic hydrogen peroxide production for methyl orange removal - Gómez Velázquez, Laura S. (2023)
Herein, we investigated the photocatalytic removal of methyl orange (MO) under 350 nm irradiation with carbon nitride (CN) nanoparticles from urea. Participation of photogenerated charge carriers and secondary reactive species in MO degradation process was evaluated by scavenging and photoelectrochemical assays. The experiments suggest that HO* radicals are not only formed from the reaction of water with photogenerated holes, but via a three consecutive one-electron reduction of O₂ involving the formation of H₂O₂. The photocatalytic MO degradation mechanism was proposed. The present results emphasize the importance of charge carriers' separation in the optimization of CN photocatalysis for technological uses.